Study of Gender in Sudden Cardiovascular Death - Rafael Emilio Araujo González; Luis Alberto Ochoa Montes; Rubén Herrera Masó; Mileidys González Lugo; Nidia Doris Tamayo Vicente; Daisy Ferrer Marrero (Revista Finlay)
Background: cardiovascular diseases represent the main cause of death in the world, specifically, sudden cardiovascular death causes the 50 % of all deaths from this cause. However, there are gender differences between the determinants that produce them. Objective: to describe the gender differences in sudden cardiovascular death according to sex in the municipality of Arroyo Naranjo, in Havana, Cuba, between 2007 and 2014. Methods: a descriptive, correlational and cross-sectional study was carried out in the Arroyo Naranjo municipality Havana, between 2007 and 2014. All cases of sudden cardiovascular death treated at the Julio Trigo López Clinical Surgical Hospital were included (N = 605). The correlation between sex and other sociodemographic factors (age, education, occupation, marital status), and between the variable sex and risk factors (diabetes mellitus, alcohol consumption, smoking, dietary habits, physical inactivity, hematocrit value and dyslipidemia). The determining differentials between men and women were applied from variables. The Chi Square statistical test and the Haberman Corrected Residuals model were used. Results: in men, the most frequent risk factors were: smoking, alcohol consumption and arterial hypertension. Women were characterized by more physical inactivity and were more affected by diabetes mellitus, dyslipidemia, and elevated hematocrit values. Conclusion: sudden cardiovascular death in the municipality of Arroyo Naranjo, Havana, in the period analyzed affected men who smoked and consumed alcohol, being more hypertensive than women. Women with greater physical inactivity were found to be more diabetic, dyslipidemic, and presented a higher reference value of hematocrit than men.